2015
DOI: 10.1007/s00340-015-6040-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of CdTe nanocrystals synthesized by a green room temperature solution method

Abstract: These materials exhibit quantum confinement effects when their sizes are comparable with the diameter of the bulk exciton, leading to split the continuum of electronic energy levels into discrete states with an effective band gap blue shifted from that of the bulk [7][8][9].There are two different synthetic methods for producing CdTe nanostructures, the organometallic route and synthesis in an aqueous solution [10][11][12][13]. The organometallic method usually requires hard conditions such as high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This specifies that CdSe QDs are encouraging materials for optical devices and confirm noticeable applications in nonlinear optics (NLO) and other areas as well. Studies by H. Naderi et al [106] depict third-order nonlinear optical properties of CdTe QDs by using the singlebeam Z-scan technique. According to particular studies' data obtained from closed-aperture z-scan, n 2 has a negative sign that shows that particular QDs exhibits self-defocusing optical nonlinearity while results of open-aperture z-scan show a positive sign of β that displays the two-photon absorption phenomenon is dominant in the intensities used for particular studies.…”
Section: Nonlinear Optical Characteristics Of Quantum Dots (Qds) and Core-shell Quantum Dotsmentioning
confidence: 99%
“…This specifies that CdSe QDs are encouraging materials for optical devices and confirm noticeable applications in nonlinear optics (NLO) and other areas as well. Studies by H. Naderi et al [106] depict third-order nonlinear optical properties of CdTe QDs by using the singlebeam Z-scan technique. According to particular studies' data obtained from closed-aperture z-scan, n 2 has a negative sign that shows that particular QDs exhibits self-defocusing optical nonlinearity while results of open-aperture z-scan show a positive sign of β that displays the two-photon absorption phenomenon is dominant in the intensities used for particular studies.…”
Section: Nonlinear Optical Characteristics Of Quantum Dots (Qds) and Core-shell Quantum Dotsmentioning
confidence: 99%
“…The design of nonlinear optical (NLO) materials with large NLO responses has been a challenge for materials scientists and chemists. In recent decades, efforts have focused mainly on inorganic semiconductor materials due to their high photochemical and photophysical stabilities (Ballesteros et al, 1999;Cotter et al, 1999;Majles Ara et al, 2015). Previous work has indicated that the third-order nonlinearity of semiconductor nanocrystals (NCs) can be enhanced by optimizing their size, shape and surface (Ballesteros et al, 1999).…”
Section: Introductionmentioning
confidence: 99%